2021
DOI: 10.3389/fcvm.2021.764599
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Perfusion Imaging After Severe COVID-19 Infection Demonstrates Regional Ischemia Rather Than Global Blood Flow Reduction

Abstract: Background: Acute myocardial damage is common in severe COVID-19. Post-mortem studies have implicated microvascular thrombosis, with cardiovascular magnetic resonance (CMR) demonstrating a high prevalence of myocardial infarction and myocarditis-like scar. The microcirculatory sequelae are incompletely characterized. Perfusion CMR can quantify the stress myocardial blood flow (MBF) and identify its association with infarction and myocarditis.Objectives: To determine the impact of the severe hospitalized COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…LGE has been reported less frequently. In a case control study on 90 hospitalized patients with troponin-positive COVID-19 infection [84], CMR performed 2 months after recovery showed post-myocarditis scar in 34% of cases and post-ischemic scar in 17% of cases. Notably, 36% of patients showed adenosine-induced regional perfusion defects.…”
Section: Cardiac Post-acute Covid-19 Syndromementioning
confidence: 98%
“…LGE has been reported less frequently. In a case control study on 90 hospitalized patients with troponin-positive COVID-19 infection [84], CMR performed 2 months after recovery showed post-myocarditis scar in 34% of cases and post-ischemic scar in 17% of cases. Notably, 36% of patients showed adenosine-induced regional perfusion defects.…”
Section: Cardiac Post-acute Covid-19 Syndromementioning
confidence: 98%
“…In most studies, recovered patients also exhibited increased or raised T2 values [4,27,29,34,35,38,41]. Finally, ECV was reported in a few studies [4,25,27,[29][30][31][32][36][37][38]41], and their pooled effect suggests that patients who recovered from COVID-19 have similar values to controls.…”
Section: Parametric Mappingmentioning
confidence: 96%
“…Studies including patients who recovered from COVID-19 reported increased [4,27,28,33,35,36], slightly increased [29,32,38,39,41] or similar [31,34] T1 native mapping values compared to controls. In particular, Kotecha et al [28], Puntmann et al [35], and Thornton et al [37] found significantly higher T1 native mapping values in large groups of recovered subjects (148, 100 and 90, respectively) compared to different control groups, including patients without myocardial injury, healthy volunteers or controls, and risk factor-matched controls [26,28,35,37]. In addition, patients who recovered from COVID-19 and had MIS-myocarditis had higher T1 native values than those with non-MIS myocarditis [30].…”
Section: Parametric Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…A return to normal of EGE within 1 month after acute myocardial inflammatory injury indicates that left ventricular function has recovered well. Myocardial perfusion imaging after severe COVID-19 also demonstrates regional ischaemia rather than global blood flow reduction[ 37 ]. Nevertheless, the biggest limitation of EGE is that it is unable to quantify SI accurately.…”
Section: Covid-19 Related Myocarditismentioning
confidence: 99%